MENGKAJI MODEL PENINGKATAN KINERJA ALIANSI STRATEGIS DAN KEUNGGULAN BERSAING UMKM - Lionora, Clarisa Alfa; Novitaningtyas, Ivo; Rahardjo, Budi; Sijabat, Yacobo P; Achsa, Andhatu; Nugroho, Ramadhani Lukman; Trisyaningsih, Melati (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2023)
This research aims to test a model for improving alliance performance and competitive advantage in MSMEs in the Borobudur area. This research uses a survey-based quantitative approach to collect primary data. The sample in this research was 44 MSMEs located in the Borobudur area and already had alliances or partners. The sampling method uses snowball sampling. Data were analyzed using multiple linear regression by SPSS. The results show that the partner selection process and relational capital can improve alliance performance of MSMEs. Furthermore, alliance performance has an influence on the competitive advantage of MSMEs. These results support the resource-based view theory and resource-dependent theory. The results provide practical implications for MSME managers in the Borobudur area to be selective in choosing suitable partners and improve the quality of relationships with partners in order to improve alliance performance, thus it can increase the competitive advantage of MSMEs.